Covenanting for Nature: A Comparative Study of the Utility and Potential of Conservation Covenants. Issue 2 (14th January 2020) - Rodgers, Christopher; Grinlinton, David
Abstract: Conservation covenants over private land are extensively used in some jurisdictions to secure a wide range of public benefits: in some cases primarily to promote nature conservation, while elsewhere to foster conservation alongside greater public access to 'green' space. This article considers the use of conservation covenants in New Zealand, Scotland, and England and Wales. It argues that they can play a unique role in balancing nature conservation, property rights and increased public access to private land. It reviews proposals for new legislation in England and Wales and argues that, if it is to be successful, the potential of conservation covenants to secure greater public access to private land should be more strongly emphasised. Their successful use in New Zealand shows that, while recognising the important balancing function that they can perform, this emphasis is critically important if covenants are to fulfil their potential to 'reconnect' people and nature.